Top Down or Bottom Up? Longitudinal assessment of the influence of professional practice gaps in gastrointestinal and endoscopic surgery on program content for the Annual Meeting of the Society of American Gastrointestinal and Endoscopic Surgeons (SAGES) (2011–2016): a report from the SAGES Continuing Education Committee (CEC) - Selzer, Don; Farrell, Timothy; Schwarz, Erin; Fu, Michael; Wu, Justin; Reyes, Angel; Selim, Niazy; McLemore, Lisa; Palter, Vanessa; Paige, John (Surgical endoscopy, 2018)
In 2016, the Society of American Gastrointestinal and Endo- scopic Surgeons (SAGES) celebrated its 35th anniversary. Since its inception, SAGES has stressed the importance of educating its members in the latest technology and tech- niques. In fact, SAGES’ mission is “to improve quality patient care through education, research, and innovation and leadership, principally in gastrointestinal and endoscopic surgery.” The SAGES Continuing Education Committee (CEC) is the organization’s clearinghouse for this effort with responsibility for overseeing major educational pro- grams including the Annual Scientific Meeting. To this end, the SAGES CEC works to enact the standards, policies, and requirements of the Accreditation Council for Continuing Medical Education (ACCME) and the American Board of Surgery (ABS). As with prior studies, this article will summarize the knowledge, competence, and performance gaps identified by attendees of a specific Annual Meeting, the 2016 SAGES Scientific Session and Postgraduate Courses held in Boston, Massachusetts. Additionally, it will expand on this analysis through the longitudinal assessment of such gaps from the 2011 through 2016 Annual Meetings in order to identify trends in these gaps over this time period.